Therapeutic Potential of Euphorbia fusiformis buch. -ham. Ex. D. Don (International Journal of Ayurveda and Pharma Research, 2022)
Nature has gifted widest range of plant diversity to India for the welfare of mankind. Plants have been utilized for various purposes by the human beings since the time immemorial. Plants have been the basic source for therapeutic preparation in the indigenous system of medicine, the Ayurveda.  With the recent changes in the life style of human being, over exploitation of natural resources has put a large number of plant species to the verge of extinction. Euphorbia fusiformis Buch. -Ham. ex D. Don (Euphorbiaceae), botanical source for the classical drug Adhoguda is one among plant species threatened with the extinction (endangered). It is a plant having potential pharmacological properties and actions. Traditionally, tribal communities have been using this plant in ethnomedicine to treat headache, arthritis, gout, paralysis, diarrhoea, abdominal diseases, abdominal tumour, liver disorders, urinary stones, chronic wounds, cracks, skin disease, eczema and poor lactation, scorpion and snake bites and plant latex as an antidote.E. fusiformis is reported to possess variety of pharmacological activities like antioxidant, antifungal, diuretic, anti-inflammatory, antibacterial, hepatoprotective, antinociceptive and galactagogue. Also, the plant has been evaluated for its use in female infertility. Present paper is an attempt to review therapeutic potential of this underexplored drug E. fusiformis.